Social impact bonds in São Paulo's state public school system: New modality of public-private partnership in Brazil: Commentary - Sergio G. Lazzarini (Arizona State University, 2020)
This article provides comments to the paper by Cássio, Goulart e Ximenes (2018), which analyzes the technical and ethical bases of the social impact bond developed in the context of the Department of Education of the State of São Paulo, Brazil, which went to public consultation in 2017. Based on facts and on the relevant technical literature, the comments raise several critical issues related to how Cássio et al. (2018) interpreted the reported events, with an emphasis on three aspects: understanding of the purposes of social impact bonds; the involvement and autonomy of the schools; and the methodology that was suggested to evaluate impact.